Teores de iodo em dietas secas e úmidas para gatos adultos comercializadas na cidade do Rio de Janeiro, Brasil - Oliveira, Priscila Cardim de; Botteon, Rita de Cassia Campbell Machado; Silva, Flávio Lopes da; Botteon, Paulo de Tarso Landgraf; Veiga, Cristiano Chaves Pessoa da (Universidade Estadual de Londrina, 2013)
Were analyzed 29 samples, 16 wet and 13 dry cat food of different flavors. The iodine levels ranged from 2.7 to 3.4 (average 2.95 mg/kg/MS) in dry food and 2.9 to 4.0 (average 3.4 mg/kg/MS) in the wet food. Eight samples (27.6%) specified on the package the assurance level (maximum) of iodine, with a dry (2.0 mg/kg/diet) and seven wet (0.04 mg/kg/diet). All non-compliant, because the values were higher than declared. Cats fed commercial diets consume proportionally more iodine in wet food than cats fed dry diets, but both with high levels of iodine. All samples analyzed were above the amounts stated on the labels. Accordingly, the wet and dry commercial food for cats show no reliable values with those reported, resulting in a possible excessive intake of this trace element for animals in question.
Contents of iodine in wet and dry foods for adult cats marketed in Rio de Janeiro, Brazil
Keywords: Cats; Feed; Food; Iodine; Nutrition